2015
DOI: 10.1038/nature15265
|View full text |Cite
|
Sign up to set email alerts
|

Controlling neutron orbital angular momentum

Abstract: The quantized orbital angular momentum (OAM) of photons offers an additional degree of freedom and topological protection from noise. Photonic OAM states have therefore been exploited in various applications ranging from studies of quantum entanglement and quantum information science to imaging. The OAM states of electron beams have been shown to be similarly useful, for example in rotating nanoparticles and determining the chirality of crystals. However, although neutrons--as massive, penetrating and neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
138
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(139 citation statements)
references
References 44 publications
0
138
1
Order By: Relevance
“…The so-called vortex (or twisted) particles with orbital angular momentum (OAM) relative to a propagation axis and the Airy beams represent the simplest examples of such non-plane-wave states. They were shown to be solutions of the wave equations [7][8][9][10][11][12][13][14], and the corresponding beams of photons, electrons, and neutrons were generated in recent years [15][16][17][18][19][20]. Vortex electrons with the kinetic energy of 200 − 300 keV can be focused to a spot of anÅngström size [21], their OAM can be as high as = 200 [22], their magnetic moment increases proportionally to [13], and this brings about new effects in the electromagnetic radiation [23,24].…”
Section: Non-plane-wave Statesmentioning
confidence: 99%
“…The so-called vortex (or twisted) particles with orbital angular momentum (OAM) relative to a propagation axis and the Airy beams represent the simplest examples of such non-plane-wave states. They were shown to be solutions of the wave equations [7][8][9][10][11][12][13][14], and the corresponding beams of photons, electrons, and neutrons were generated in recent years [15][16][17][18][19][20]. Vortex electrons with the kinetic energy of 200 − 300 keV can be focused to a spot of anÅngström size [21], their OAM can be as high as = 200 [22], their magnetic moment increases proportionally to [13], and this brings about new effects in the electromagnetic radiation [23,24].…”
Section: Non-plane-wave Statesmentioning
confidence: 99%
“…Another related new development has been the production of twisted matter (de-Broglie) waves. Such matter waves have been realized for electrons and neutrons and proposed for atoms [11][12][13][14][15][16][17][18][19][20]. It has been shown that the diffraction of an atom wave packet from a light mask with a forklike intensity profile results in the generation of atom vortex Bessel and LG beams endowed with the property of quantized orbital angular momentum [19].…”
Section: Introductionmentioning
confidence: 99%
“…Such a twisted photon, |ω, k z , κ, ℓ, λ⟩, is a (paraxial) monochromatic state with the OAM ℓ, a helicity λ, a longitudinal momentum k z , and an absolute value of the transverse momentum κ. During the last several years, 200-300-keV electrons and cold neutrons carrying the OAM were also generated [9,10,11,12], along with the so-called Airy photons and electrons [13,14] and their different generalizations. Possible applications of these states to the hadronic physics have been discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%